The Effectiveness of the Project-Based Learning Model Based on Autodesk Inventor on Students’ Learning Outcomes in the Manufacturing Engineering Drawing Subject at SMK Negeri 1 Padang - Oktorio Yumiko; Mulianti Mulianti (Darul Yasin Al Sys, 2026)
Project-based learning supported by digital design technology has become increasingly relevant in vocational education; however, empirical evidence on its application with Autodesk Inventor in Manufacturing Engineering Drawing remains limited. This study aims to evaluate the effectiveness of the Autodesk Inventor-based Project-Based Learning model in improving students’ learning outcomes in the Manufacturing Engineering Drawing subject at SMK Negeri 1 Padang. A quantitative approach with a quasi-experimental non-equivalent control group design was employed. The participants consisted of 40 Grade XI Mechanical Engineering students selected through purposive sampling and divided into an experimental class and a control class. Data were collected through pretest, posttest, and documentation and were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, and paired sample t-test with the assistance of SPSS. The findings indicate that both classes experienced significant improvement; however, the experimental class achieved a higher mean score increase than the control class. The experimental class improved from 48.30 to 66.85, whereas the control class improved from 44.25 to 57.55. The posttest comparison showed a 16.15% difference in favor of the experimental class. The study concludes that Autodesk Inventor-based Project-Based Learning is effective in improving students’ learning outcomes in vocational technical drawing. These findings provide practical implications for vocational education by highlighting the importance of integrating project-based pedagogical models with digital design technology to support more effective learning in Manufacturing Engineering Drawing.